Engineering of osteogenic construct using rat bone marrow stromal-derived osteoblasts seeded on poly(caprolactone-trifumarate)scaffold / Chai Yoke Chin - Chai, Yoke Chin (2006)
The application of external fixators in hand surgery is a well established technique which is restricted by the accessibility and price of the system. The purpose of this study was to develop a low-cost and lightweight external finger fixator that is able to restore full function and dynamic range of motion of a contrature finger joint that is caused by traumas. The process included radiographic measurements of a finger joint, conversion of Computer Tomography (CT) images geometrical hand-modelling in the Computer Aided Design(CAD) system, external finger fixator design, virtual simulation of the new fixator design, determination of finger-fixator matching, and manufacturing on a Computer Numerically Controlled (CNC) machine. The outcome of this engineering process was a surgical application of the fixator to cadaveric specimens. The new external finger fixator consists of proximal, middle and distal phalangeal support sections, each connected rigidly to a hinge that connect each support section and its corresponding phalangeal attachment through the movement of flexion and extension. The hinge is controlled by a long threaded rod that is turned gradually by a knob in a clockwise or counter clockwise direction. Software simulation, including finite element analysis was carried out and the outcome was supported by testing on cadayeric specimen to examine the effectiveness of the fixator. This research utilize a novel breakthrough design in developing the new external finger fixator. The new external fixation device reduces contractures of the proximal interphalangeal(PIP) and distal interphalangeal (DIP) joints by soft tissues distraction and a simple surgical procedure.